War on Terror in Regional and Trans-Regional Context (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Terrorism from the longer time has attracted many of the experts in history and present times to work on it with a quest to find out the causes and look for its cure. This article, I have made an endeavor to discuss terrorism from different aspects examining the history of the creation of different terrorist organizations; the research analyzes the latest Talibanization phenomenon. Before and after the 9/11 tragedy, there had been many discussions that seemed to have pondered upon Good Talibans and Bad Talibans, the study intends to make sense to both these terminologies by giving each of it sufficient time to have a clear understanding by examining through rich literature that illustrates both these terminologies candidly and categorically. The work on this topic is one of its kind that is unbiased that not only explains the mistakes being committed by the countries where the rogue elements like Al-Qaida and Taliban prevailed or are still prevailing, Though Afghanistan is in the focus but it has also pointed out the wrong policy decisions in different phases of time by the United States of America during the fight against terrorism.